Reception of Mythological Image of the Bird at Bunin Cycle «The Bird's Shadow» - MAHBOBZADH, Sara; NASRUTDINOVA, Liliya Harisovna; NASRUTDINOVA, Liliya Harisovna; YAHYAPOUR, Marzieh; YAHYAPOUR, Marzieh (Utopía y Praxis Latinoamericana, 2020)
ABSTRACT The article notes that the writer's interest in the East in tune with the typical art of the silver age trends about the Indo-European origins of russian culture, which is associated with reflections on the essence of its intermediate (between East and West). The writer's choice of an unusual genre modification – "travel poem" – allows him to create a multi-level artistic image of the eastern city. The analysis of the cycle by I.A. Bunin "The Bird's Shadow" testifies to the divergence of his interpretation of the image of the mythical bird Huma with the context of the Russian Silver age and rapprochement with the Eastern tradition.RESUMEN El artículo señala que el interés del escritor en Oriente está en sintonía con el arte típico de las tendencias de la edad de plata sobre los orígenes indoeuropeos de la cultura rusa, que se asocia con reflexiones sobre la esencia de su intermedio (entre Oriente y Occidente). La elección del escritor de una modificación de género inusual - "poema de viaje" - le permite crear una imagen artística de varios niveles de la ciudad oriental. El análisis del ciclo por I.A. Bunin " la sombra del pájaro " da testimonio de la divergencia de su interpretación de la imagen del mítico pájaro Huma con el contexto de la edad de plata rusa y el acercamiento con la tradición oriental.